SUSTAINABLE BANKING PRACTICES AND FINANCIAL PERFORMANCE - AN EMPIRICAL STUDY ON ESG INTEGRATION IN PRIVATE BANKING SECTOR IN CHENNAI - Maheswari, R. Uma (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The study examines the range of ESG integration and their effectiveness in improving the sustainability banking practices of private sector banks and also focuses on assessing the impacts of sustainability banking practices on financial performance empirically using the perception of banking employees. This study employs an empirical research design to investigate the range and effectiveness of ESG integration in private sector banks in Chennai. The Z formula enables to attain the sample size of 269 which is significant to get reliable results from the study. A proportionate random sampling technique was used to select participants from the population of employees in private sector banks in Chennai. This technique ensures that the sample is representative of the population in terms of the proportion of employees from different banks. The primary data was collected through a structured interview schedule administered to the selected sample of banking employees. The collected data will be analyzed using the following statistical tools of Percentage Analysis, Chi-Square Test and Path Model. Key findings highlight the positive impact of specific sustainability practices such as reducing collateral wastages on financial performance while also indicating areas for improvement, particularly in ESG risk assessment.